DNA template sequence control of bacterial RNA polymerase escape from the promoter - Heyduk, Ewa (Nucleic Acids Res, 2018)
Promoter escape involves breaking of the favourable contacts between RNA polymerase (RNAP) and the promoter to allow transition to an elongation complex. The sequence of DNA template that is transcribed during promoter escape (ITS; Initially Transcribed Sequence) can affect promoter escape by mechanisms that are not yet fully understood. We employed a highly parallel strategy utilizing Next Generation Sequencing (NGS) to collect data on escape properties of thousands of ITS variants. We show that ITS controls promoter escape through a combination of position-dependent effects (most prominently, sequence-directed RNAP pausing), and position-independent effects derived from sequence encoded physical properties of the template (for example, RNA/DNA duplex stability). ITS often functions as an independent unit affecting escape in the same manner regardless of the promoter from which transcription initiates. However, in some cases, a strong dependence of ITS effects on promoter context was observed suggesting that promoters may have ‘allosteric’ abilities to modulate ITS effects. Large effects of ITS on promoter output and the observed interplay between promoter sequence and ITS effects suggests that the definition of bacterial promoter should include ITS sequence.